-5a-2=3(a-6)

Simple and best practice solution for -5a-2=3(a-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5a-2=3(a-6) equation:


Simplifying
-5a + -2 = 3(a + -6)

Reorder the terms:
-2 + -5a = 3(a + -6)

Reorder the terms:
-2 + -5a = 3(-6 + a)
-2 + -5a = (-6 * 3 + a * 3)
-2 + -5a = (-18 + 3a)

Solving
-2 + -5a = -18 + 3a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-3a' to each side of the equation.
-2 + -5a + -3a = -18 + 3a + -3a

Combine like terms: -5a + -3a = -8a
-2 + -8a = -18 + 3a + -3a

Combine like terms: 3a + -3a = 0
-2 + -8a = -18 + 0
-2 + -8a = -18

Add '2' to each side of the equation.
-2 + 2 + -8a = -18 + 2

Combine like terms: -2 + 2 = 0
0 + -8a = -18 + 2
-8a = -18 + 2

Combine like terms: -18 + 2 = -16
-8a = -16

Divide each side by '-8'.
a = 2

Simplifying
a = 2

See similar equations:

| 760-50h=0 | | -9.7(1.7x-5)+6= | | .16x+.8(x-4)=.01(3x-2) | | 3+2x=2(2x+2)-3(x-3) | | 3(2x-6)=4(x+2) | | 2w+2(4x-7)=86 | | 7m+12/8=2m-1/3 | | 4p^2=-9p-2 | | 3x-1+x+x=6.4 | | 3(2x-6)=-4(x-2) | | c^2=33 | | -z-3.2=-22.8+3z | | 0.05(342-x)+0.07x=72 | | 2x+2(x-1)=2x-16+3x | | 3(2x-4)=-4(x-2) | | 16x^2=144-9y^2 | | (10m)/(5m) | | 4x=-2(3x-5) | | z^3-3iz^2-3z+i+1=0 | | 10m/5m | | -9x+12x-10-4x-2x=47 | | 0.3x+0.4=0.9x-1.4 | | 3x^2-8k=16 | | 2y-10x^2+4=0 | | 8+3m-3=9m+12-5m | | 4t-6=12t-24+18 | | 78+3x=10x-97 | | 6/z-3/z=15 | | 2(2x-3)=4(2x+2) | | 12-x/2=x/5 | | 2x-5/12-3x/6=11/12 | | 4x^2-2x+30=0 |

Equations solver categories